Sistem Informasi Sistem Informasi Penyewaan Bus Pariwisata Berbasis Web Pada PT Asli Prima Inti Karya - Wahyuddin; Ahmad Kautsar; Renaldy Frans Sutisna (Universitas Nusa Putra, 2022)
The existence of tourism facilities and infrastructure are elements to facilitate the process of tourism activities. With the facilities and infrastructure, it is hoped that tourism activities can run smoothly. Among the facilities in tourism activities are transportation/tour buses, travel operators, travel agents, restaurants, hotels/inns, tourist attractions, and tourist attractions. PT Asli Prima Inti Karya is a company engaged in tourism bus rental services, located in Pandeglang Regency, precisely in Labuan, Banten province. PT Asli Prima Inti Karya organizes several tour package and travel agency activities. The conventional bus rental system did not initially cause problems in terms of service. Along with the increasing demand for rental, it takes a complete service so that customers can be served well. The author analyzes the problem and makes a bus rental application design as a solution to the problems in serving customers who will rent buses. The application design uses UML, and uses the Sublime Text 3 programming language, PHP, XAMPP Version 3.2.4, and the database used is MySQL. The results of the application test show that the existence of this information system can make it easier for tenants to carry out the bus rental process.